THE PROTECTIVE EFFECT OF AN AQUEOUS EXTRACT FROM SMILAX EXCELSA L. AGAINST CARBON TETRACHLORIDE-INDUCED LIVER INJURY IN RATS - Ozsoy, Nurten; Okyar, Alper; Arda-Pirincci, Pelin; Can, Ayse; Bolkent, Sehnaz; Akev, Nuriye (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Because reactive oxygen species (ros) contribute to the pathogenesis of various acute and chronic liver diseases,dietary antioxidants and drugs from herbal origins have been proved to be beneficial as therapeutic agents in reversing hepatotoxicityand oxidative stress. The objective of this study was to investigate the protective effect of an aqueous extract from smilax excelsa l.Shoots and leaves against acute ccl4-induced liver injury as well as the changes in antioxidative defense system in female wistaralbino rats.Materials and Methods: S. Excelsa extract was administered orally in doses of 100, 200 and 400 mg/kg body weight, once daily for9 days. Acute hepatic toxicity was induced by intraperitoneal injection of ccl4 (1 ml/kg) on the 10th day. 24 h after ccl4 intoxication,biochemical and histopathological analyses were undertaken on sera and liver tissues.Results: Ccl4 challenge caused significant increases in the activities of liver enzymes as well as the levels of bilirubin,malondialdehyde and nitric oxide, while total serum protein levels and antioxidant defense system parameters were reducedsignificantly compared to the normal group. Administration of s. Excelsa extract at a dose of 400 mg/kg resulted in a suppression ofccl4-induced lipid peroxidation and altered oxidative stress parameters to nearly normal values in comparison to ccl4-treated rats.Nevertheless the extract did not reduce the extent of ccl4-induced mild liver injury, as seen by the histopathology of liver damage.Conclusion: The results of this study suggest that s. Excelsa could protect the liver tissues against ccl4-induced oxidative stressprobably by increasing antioxidative defense activities.